Productivity of ranch N'Dama cattle under trypanosomiasis risk - Feron, A.; D'Ieteren, G.D.M.; Durkin, J.W.; Kakiese, O.; Maehl, J.H.H.; Mulungo, M.; Nagda, S.M.; Paling, R.W.; Pelo, M.; Rarieya, J.M.; Sheria, M.; Thorpe, W.R.; et al. (ILCA/ILRAD, 1988)
Discusses the productivity of N;Dama cattle at Kolo and Mushie ranches (Zaire). Includes data on productivity under zero (Kolo) and high (Mushie) trypanosomiasis risk (1984-86). Compares the productivity of Boran and N'Dama cattle under ranch management at five sites in Africa.